Huma Betang's Philosophy: Interreligious Harmony and Weaving of National Identity in Palangka Raya - Pattiasina, Sharon Michelle O. (IAIN Palangka Raya, 2025)
The diversity of ethnicities, religions, and cultures in Palangka Raya creates complex social dynamics, which have the potential to pose challenges to social integration and community cohesion. The study aimed to analyze how the huma betang philosophy is implemented in interactions between communities across religions and cultures, and its contribution to weaving national identity in a multicultural context. The study used a qualitative approach with a phenomenological method, through observation techniques, in-depth interviews, and literature studies. The study showed that the huma betang philosophy, along with the motto Bumi Tambun Bungai, Bumi Pancasila, is the basis of values ​​in building inclusive social relations between the Dayak community and immigrant groups. The values ​​of huma betang are not only carried out in the internal Dayak community but are also experienced as an ethic of living together that emphasizes solidarity, tolerance, and humanity across identities. The particular study contributes to a theoretical understanding of the role of local values ​​in strengthening social cohesion and national identity in a pluralistic society.